MEDICAL ASSISTANCE IN DYING (MAID): A Policy Analysis to Provide Greater Clarity for Social Workers in Practice in Ontario - Amurao, Alona (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2019)
Medical Assistance in Dying (MAID) is a legal federal framework for medical practitioners to assist in the cessation of life upon request from eligible patients who seek assisted death in order to die peacefully and with dignity. MAID’s ‘mentally competent’ eligibility criteria currently create confusion for social workers because they provide little guidance on how to best implement the desired practices intended to support the aims of MAID. Secondly, current criteria pose challenges for vulnerable populations, particularly patients with amyotrophic lateral sclerosis (ALS). ALS patients who are deemed mentally incapable are denied access to MAID, suffering in pain every day until they die. Canada’s MAID policy infringes on their autonomy, and removes their choice to die with dignity. This injustice calls for further reconsideration of the ways MAID can be reformed to serve dying Canadians who are falling through the cracks of MAID. Policy recommendations include inclusion of advanced directives and substitute decision makers. Due to this unequal access in health care services, this concern constitutes a social work issue. Recommendations for social work include increasing competency, and advocacy regarding the provision of MAID.